Methodological framework for the axiological paradigm in the learning environment - Dauyenov, Yernur; Zhumataeva, Engilika; Orynbekova, Ainur (Frontiers in Education, 2022)
Modern conditions of education require the development of new methodological approaches for the implementation of the educational process. The purpose of study is to analyze the axiological paradigm in the Kazakhstan’s system of teacher training and determines experimentally the phases of its development in Kazakhstan in early 21st century. A total of 284 students participated in the experiment. The findings suggest that students in the control group repeated what was said during the lecture. Generally, they did not go beyond repetitions. Out of 142 students who were involved in the first phase of the experimental group, 80 students responded at the heuristic level, 12 students responded at the innovative level, and 8 students responded at the creative level. Students in the experimental group were capable of independent thinking beyond lectures. 8 students proved to be 40% capable of drawing conclusion to an unusual, phenomenally high degree. Practical implications and further research might focus on the special aspects of developing the axiological paradigm not only for students in Kazakhstan, but also in other countries in a comparative aspect. New research can also rely on the experiment’s methodological framework.